A Case of Segmental Aplasia of the Uterus, Cervix, and Cranial Vagina in a Cat - Souther, Samantha; Baik, Nam Joo; Clapp, Kemba; Nappier, Mike; Sponenberg, D. Phillip; Cecere, Julie (Frontiers in Veterinary Science, 2019)
This case documents a rare set of congenital anomalies that resulted in an atypical cystic lesion in the cranial vagina of a queen. A discrete cystic lesion was identified in an 8 year old intact female domestic shorthair cat presenting for routine ovariohysterectomy. Morphological, radiographic, and histopathological findings were consistent with segmental aplasia of the uterus, cervix, and vagina resulting in a blind dilation of the cranial vagina. Segmental vaginal aplasia in combination with the failed canalization of the cervix resulted in a blind portion of the cranial vagina, in which normal secretions collected and became inspissated. This formed a discrete cystic structure. This case represents a novel combination and clinical presentation of segmental aplasia in the cat, involving both the uterus and cranial vagina. Ovariohysterectomy was performed for sterilization and a partial vaginectomy was performed to remove the cystic lesion in its entirety.